Specific Characteristics of the Crime of Robbery by Employment or Distribution - Marufaliyev is the son of Ahrorbek Avazbek; Jamoldinov is the son of Khumoyun Bakhtiorbek (European Journal of Life Safety and Stability (2660-9630), 2024)
This article analyzes the characteristic features of the crime of embezzlement or robbery, its concept, its social danger, and the history of its development. The article also discusses the scientific debate with the views of national and foreign scientists. The legislation of foreign countries on the crime of embezzlement or expropriation was studied, and proposals and recommendations for national legislation were developed.